1. The problem statement, all variables and given/known data 2. Relevant equations Gamma(n+1) = n(gamma(n)) 3. The attempt at a solution I have searched around trying to figure out how to do this. So far I have come out with: Gamma(n) = (n-1)(n-2)... Gamma(n+1)=n(n-1)(n-2)...2(1) otherwise known as Gamma(n+1)=n! Problem is... I don't fully understand what I did because I followed a like example. Can someone please help me out with this. Also I have not even attempted the second part, so ignore that for now.